Multiple Intelligence Learning-Based Education Management For Students With Special Needs - Badrus Soleh; Ulum Munawwaroh (JIEMAN: Journal of Islamic Educational Management, 2023)
The leadership of the school principal in an effort to improve the quality of education is closely related to the strategy he carries out, so that the principal's strategy is a determinant of whether or not the quality of a school institution is good. The purpose of this study was to determine strategic planning, strategy implementation, and evaluation of school principal strategies in improving the quality of education at MTs Negeri 1 Kotawaringin Timur. The research method is qualitative with a case study approach, collecting data by observation, documentation, and interviews. The results of the research are: (1) Planning for school principals is guided by regulations and refers to the Vision and Mission and goals of the school, conducting an analysis before formulating the program. The strategy set is: a). Teacher Competency Improvement, b). Development and Maintenance of Facilities and Infrastructure, c). Budget Management Efficiency and Effectiveness, d). Discipline and Development of outstanding students, e). Activity Publication. (2) Implementation of the program that has been selected, namely through the process of analysis, communication and coordination with all fields. In implementation, the principal supervises directly the implementation of the program, with the aim of being able to directly address the obstacles found. (3) Evaluation and supervision is carried out directly by supervising the areas of each program. Through a quality assurance agency, the school principal can carry out an evaluation based on the report data for each program implementation. Penelitian ini bertujuan untuk mendeskripsikan perencanaan, pengorganisasian, pelaksanaan dan pengawasan manajemen pendidikan berbasis multiple intelligence learning pada peserta didik berkebutuhan khusus serta mengetahui faktor pendukung dan penghambat dalam implementasi manajemen. Penelitian ini merupakan penelitian kualitatif  fenomenologi di SLB Asih Mulya Gurem Pamekasan melalui Teknik wawancara, observasi dan dokumentasi. Subjek penelitian ini adalah Kepala sekolah dan guru pendamping Anak Berkebutuhan Khusus (ABK). Hasil penelitian menyimpulkan bahwa: Pertama, manajemen pendidikan berbasis multiple intelligence learning pada peserta didik berkebutuhan khusus di SLB Asih Mulya Gurem Pamekasan meliputi: 1) Perencanaan pembelajaran ABK dilaksanakan sesuai dengan konsep pembelajaran di sekolah luar biasa, yaitu dengan menggunakan RPP dan silabus; 2) pengorganisasian pembelajaran dengan penetapan surat keputusan kepala sekola terkait pembagian tugas mengajar, wali kelas, tim teaching dan pendamping ABK; 3) pelaksanaan pembelajaran ABK dilaksanakan di ruang kelas dengan melaksanakan hal-hal yang telah direncanakan; 4) pengawasan pembelajaran ABK dilaksanakan oleh kepala sekolah dengan melakukan supervisi dan evaluasi pembelajaran setiap bulan. Kedua, faktor pendukungnya yakni penggunaan alat peraga oleh pendidik dalam proses pembelajaran agar anak dapat menegerti dan semangat. Ketiga, faktor penghambatnya yakni antara lain: orang tua yang tidak mau menyekolahkan anaknya yang memiliki kebutuhan khsus, pendidik yang kadang tidak memahami perbedaan karakter dari masing-masing peserta didik, dan peserta didik yang merasa jenuh saat pembelajaran.